Ollie Moore interviewed by John Meredith and Rob Willis in the John Meredith folklore collection - Moore, Ollie, 1906-; Meredith, John, 1920-2001.; Willis, Rob, 1944- (1987)
Folkloric recording.
Conversation: his musical abilities -- Accordion: varsoviana; mazurka, Clementine; polka, My name is Jerry; waltz medley, Irish Eyes, Come back to Erin, Lassie from Lancashire; Lancers, Yankee Doodle, Nelly Grey, Wearing of the Green, Golden Slippers; Alberts, Redwings, Swannee River, Merry Widow; Barn dance, Drover's dream, John Brown's body, Who's your lady friend, All by yourself, Harrigan; Quickstep, Misery Farm, The Saints, Roll 'em girls, In your green hat. Singing: Roll 'em girls; The Collier.
Recorded at Swan Hill, New South Wales on 2 April 1987.
Also available online
Keywords: Moore, Ollie, -- 1906- -- Interviews; Accordion music; Folk dance music -- Australia; Folk songs, English -- Australia; Folklore -- Australia